Risk factor for covid-19 patients on ventilators at gatot soebroto army hospital - I Wayan Agus Putra; Teja Koswara; Muhammad Alif Rafi (ACTA Medical Health Sciences, 2023)
COVID-19 is a disease caused by the SARS-CoV-2 virus. More than 90% of patients on ventilators with COVID-19 infections develop pneumonia, and 40% develop ARDS. The severity of the disease is influenced by a number of variables, such as age and comorbid factors. In July 2021, Indonesia experienced a very high increase, namely 948,467 new positive cases and 20,877 deaths. This study aimed to identify the risk factors for COVID-19 patients on ventilators at the Gatot Soebroto Army Hospital. The descriptive research method was employed. Data collection was taken from medical records. The sample in the study was 76 people who were COVID-19 patients on ventilators at the Gatot Soebroto Army Hospital from July to September 2021. The majority of COVID-19 patients were adults (60.5%) and male (53.9%). The results of the CT-value examination showed 63.2% of patients had CT values <29 (strong positives). The results of the D-dimer examination found that 94.7% of patients had abnormal results ≥500 ng/dL, and the results of the radiological examination found that 96.1% of patients indicated pneumonia. Patients with comorbid conditions included 46.1% with diabetes mellitus, 44.7% with hypertension, 31.6% with obesity, and 5.3% with cardiovascular disease. It was found that 80.3% of patients died at the end of treatment. DOI : 10.35990/amhs.v2n1.p29-37 REFERENCE Ciotti M, Ciccozzi M, Terrinoni A, Jiang W, Wang C, Bernardini S, et al. The COVID-19 pandemic. Crit Rev Clin Lab Sci [Internet]. 2020;0(0):1–24. Available from: https://doi.org/10.1080/10408363.2020.1783198 Susilo A, Rumende CM, Pitoyo CW, Santoso WD, Yulianti M, Herikurniawan H, et al. Coronavirus Disease 2019: Tinjauan Literatur Terkini. J Penyakit Dalam Indones. 2020;7(1):45. Indonesia KKR. Peta Sebaran Transmisi Lokal dan Wilayah Terkonfirmasi [Internet]. Infeksi Emerging. 2022. Available from: https://infeksiemerging.kemkes.go.id/dashboard/covid-19 Aqmarina NW, Risanti ED, Mahmudah LN, Jatmiko SW. Obesitas Sebagai Faktor Risiko Keparahan Pada Covid-19. Proceeding of The URECOL. 2021;(Nov):371–7. Rahayu LA, Admiyanti JC, Khalda YI, Adha FR, Agistany NFF. Hipertensi, Diabetes Melitus dan Obesitas Sebagai Faktor Komorbiditas Utama Terhadap Mortalitas Pasien Covid-19: Sebuah Studi Literatur. J Ilm Mhs Kedokt Indones. 2021;9:90–7. Sista K. Waspadai Obesitas dan Pengaruhnya Terhadap Keparahan Penyakit COVID-19 [Internet]. RSUP dr. Soeradji Tirtonegoro. 2020 [cited 2022 Jul 6]. Available from: https://rsupsoeradji.id/waspadai-obesitas-dan-pengaruhnya-terhadap-keparahan-penyakit-covid-19/ Yanti B, Hayatun U. Peran Pemeriksaan Radiologis Pada Diagnosis Coronavirus Disease 2019. J Kedokt Syiah Kuala. 2019;20:53–7. Wijayanti LE, Aryani D, Wahyu S. Hubungan Nilai CT Pada Pasien Terkonfirmasi COVID-19. J Kesehat Tambusai. 2022;3:96–103. Permana A, Yari CE, Aditya AK. Gambaran D-Dimer Dan Limfosit Pada Pasien Terkonfirmasi COVID-19 di RS Haji Jakarta. J Ilm Anal Kesehat. 2021;7(1):62–71. Wahyu W, Putra S. Hubungan Konsentrasi Serum C-Reactive Protein dan D-Dimer dengan Derajat Keparahan dan Mortalitas Pasien COVID-19. Intisari Sains Medis. 2021;12(2):680–5. Putri NAP, Putra AE, Mariko R. Hubungan Usia, Jenis Kelamin dan Gejala dengan Kejadian COVID-19 di Sumatera Barat. Maj Kedokt Andalas. 2021;44(2). Elviani R, Anwar C, Sitorus RJ. Gambaran Usia pada Kejadian COVID-19. J Unja. 2021;277:6–11. Siappa O, Pratiningrum M. Hubungan Gejala Klinis dengan Nilai CT pada Pemeriksaan Real-time PCR SARS-CoV-2. J Ked Mulawarman. 2021;8(April):89–99. Matsushita K, Marchandot B, Jesel L, Ohlman P, Morel O. Impact of COVID-19 on the Cardiovascular System: A Review. J Clin Med. 2020. Willim HA, Ketaren I, Supit AI. Dampak Coronavirus Disease 2019 terhadap Sistem Kardiovaskular. e-CliniC. 2020;8(28):237–45. Hobohm L, Sagoschen I, Barco S, Schmidtmann I, Espinola-Klein C, Konstantinides S, et al. Trends and Risk Factors of In-Hospital Mortality of Patients with COVID-19 in Germany: Results of a Large Nationwide Inpatient Sample. Viruses. 2022;14(2). Fitri IC, Singh G, Amin Z. Diagnosis Banding Ground Glass Opacities Pada CT-Scan Toraks di Era COVID-19. Indones J Chest. 2021;8(1):37–58. Petrovic V, Radenkovic D, Radenkovic G, Djordjevic V. Pathophysiology of Cardiovascular Complications in COVID-19. Front Physiol. 2020;11(October):1–11. Putra MK, Utariani A, Soemartono C, Semedi BP, Hardiono. Penggunaan Ventilatory Ratio dan Alveolar Dead Space Fraction sebagai Prediktor Mortalitas pada Pasien COVID-19 dengan Acute Respiratory Distress Syndrome. J Anestesi Perioper. 2021;9(1):10–7. Suryaputra GP, Apriningsih H, Wardani MM. Hubungan Komorbid dengan Mortalitas dan Lama Rawat Inap pada Pasien COVID-19 di Rumah Sakit UNS Surakarta. Plex Med J. 2022;1(1):32–41. Karya KWS, Suwidnya IM, Wijaya BS. Hubungan Penyakit Komorbiditas terhadap Derajat Klinis COVID-19. Intisari Sains Medis. 2021;12(2):708–17.